Proteasome and Neuroprotective Effect of Hyperbaric Oxygen Preconditioning in Experimental Global Cerebral Ischemia in Rats - Ostrowski, Robert P.; Pucko, Emanuela; Matyja, Ewa (Frontiers in Neurology, 2022)
Objectives: We investigated the involvement of proteasome in the mechanism of preconditioning with hyperbaric oxygen (HBO-PC). Methods: The experiments were performed on male Wistar rats subjected to a transient global cerebral ischemia of 5 min duration (2-vessel occlusion model), and preconditioned or not with HBO for 5 preceding days (1hr HBO at 2.5 ATA daily). In subgroups of preconditioned rats, the proteasome inhibitor MG132 was administered at 30 min prior to each preconditioning session. 24 hrs and 7 days post-ischemia, after neurobehavioral assessment, the brains were collected and evaluated for morphological changes and quantitative immunohistochemistry of cell markers and apoptosis-related proteins. Results: We observed a reduced damage of CA1 pyramidal cells in the HBO preconditioned group only at 7 days post ischemia. However both at early (24hrs) and later (7 days) timepoints, HBO PC enhanced the tissue expression of 20S core particle of the proteasome and of the nestin, diminished astroglial reactivity, and reduced p53, PUMA and BIM expression in the hippocampus and cerebral cortex. HBO-PC also improved T-maze performance at 7 days. Proteasome inhibitor abolished beneficial effects of HBO-PC on postischemic neuronal injury and functional impairment, and reduced the ischemic alterations in the expression of investigated proteins. Significance: HBO-PC-induced brain protection against severe ischemic brain insult appears to involve the proteasome, which can be linked to a depletion of apoptotic proteins and improved regenerative potential.